2004
DOI: 10.1073/pnas.0400604101
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling with arrays of randomly disrupted genes in mouse embryonic stem cells leads to in vivo functional analysis

Abstract: DNA arrays are capable of profiling the expression patterns of many genes in a single experiment. After finding a gene of interest in a DNA array, however, labor-intensive gene-targeting experiments sometimes must be performed for the in vivo analysis of the gene function. With random gene trapping, on the other hand, it is relatively easy to disrupt and retrieve hundreds of genes͞gene candidates in mouse embryonic stem (ES) cells, but one could overlook potentially important gene-disruption events if only the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 26 publications
2
38
1
Order By: Relevance
“…For example, the average gene disrupted by LNPAT1 encoded 1268 nt of exon sequence of which an average of 596 nt of exon sequence was located downstream of the provirus. These results are similar to those that have been described for the related RET poly(A) trap vector (Matsuda et al 2004), but are at odds with studies involving VICTR3 and VICTR20 in which 44% of the integration events were reported to be near the 5Ј-ends of cellular genes (Zambrowicz et al 1998). Additional experiments will be required to identify factors that may influence the expression of fusion transcripts with multiple downstream exons.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…For example, the average gene disrupted by LNPAT1 encoded 1268 nt of exon sequence of which an average of 596 nt of exon sequence was located downstream of the provirus. These results are similar to those that have been described for the related RET poly(A) trap vector (Matsuda et al 2004), but are at odds with studies involving VICTR3 and VICTR20 in which 44% of the integration events were reported to be near the 5Ј-ends of cellular genes (Zambrowicz et al 1998). Additional experiments will be required to identify factors that may influence the expression of fusion transcripts with multiple downstream exons.…”
Section: Discussioncontrasting
confidence: 43%
“…LNPAT1 (Fig. 1) consists of the gene trap elements from the previously described RET vector (Ishida and Leder 1999) (with the longer Pol II promoter sequence [Matsuda et al 2004]) placed between heterotypic recognition sites (loxP and lox5171) for the Cre DNA site-specific recombinase (Lee and Saito 1998). An RNA instability region from the human GM-CSF gene is intended to suppress the expression of unspliced transcripts, providing further selection for cells that express properly spliced fusion transcripts.…”
Section: Replaceable 3ј Gene Trap Vectorsmentioning
confidence: 99%
“…Briefly, for each assay, cells were washed with phosphate-buffered saline, diluted in annexin V binding buffer containing annexin V and PI, and incubated for 15 min at room temperature in the dark. The cells were analyzed by fluorescence-activated cell sorting (BD Biosciences) as described previously (23), with the acquisition of a total 10,000 events/sample to ensure adequate data.…”
Section: Methodsmentioning
confidence: 99%
“…A 8.8 kb fragment and a 1.3 kb fragment, obtained by PCR, were used as the long and short arms for the targeting vector. The resulting targeting vector was linearized with XhoI digestion and introduced into RF8 ESCs by electroporation and selected with G418 (200 g/ml) according to the protocol described (16). Genomic DNAs from G418-resistant colonies were screened for homologous recombination by Southern blotting and PCR.…”
Section: Methodsmentioning
confidence: 99%
“…Cell Culture, siRNA, and Transient Transfection-Mouse RF8 ESCs were maintained on mitomycin-treated mouse embryonic fibroblasts (MEFs) in standard ESC culture medium (DMEM, 15% fetal bovine serum, 2 mM L-glutamine, 100 M nonessential amino acids, 1% penicillin and streptomycin, and 0.1 mM ␤-mercaptoethanol), as previously described (16). ESCs were transfected with 50 nM CIBZ-specific or scrambled negative control Dicer substrate siRNA duplexes (Integrated DNA Technologies), as described previously (18).…”
Section: Methodsmentioning
confidence: 99%